Independent and joint influence of depression and advanced lung cancer inflammation index on mortality among individuals with chronic kidney disease - Zhou, Jie; Liu, Wenjun; Liu, Xiaoxin; Wu, Jijun; Chen, Ying (Frontiers in Nutrition, 2024)
Background: The combined effect of depression and nutritional-inflammatory status on mortality in the chronic kidney disease (CKD) population is unclear. Methods: We prospectively analyzed 3,934 (weighted population: 22,611,423) CKD participants from the National Health and Nutrition Examination Survey (2007-2018). Depression and nutritional-inflammatory status were assessed with Patient Health Questionnaire 9 (PHQ-9) and Advanced Lung Cancer Inflammation Index (ALI), respectively. Weighted multivariate COX regression models, restricted cubic splines (RCS) models, and stratified analyses were used to investigate the association of PHQ-9 scores and ALI with all-cause mortality. Results: During a median follow-up of 5.8 years (interquartile range 3.4-8.6 years), a total of 985 patients died (25.0%). Each point increase in a patient's PHQ-9 score increased the risk of all-cause mortality by 4% (HR, 1.04; 95% CI, 1.02-1.06; p< 0.001), in the full adjusted model. However, an increase in ALI levels was associated with a decreased risk. HRs (95% CI) of 0.76 (0.65-0.90), 0.70 (0.57-0.86), and 0.51 (0.41-0.64) in the Q2, Q3, and Q4 of ALI compared with the Q1 of ALI, respectively. In addition, the joint analysis showed that CKD patients without depression and with higher ALI were associated with a reduced risk of all-cause mortality. Namely, patients in the highest ALI group (Q4) without depression had the lowest risk (HR, 0.32; 95% CI, 0.21-0.48). Furthermore, this combined effect was consistent across all subgroups, and no significant interaction was found (p >0.05 for interaction). Conclusions: In a nationally representative sample of US patients with CKD, coexisting depression and poorer nutrition-inflammation were associated with a significantly increased risk of all-cause mortality.